Environment at the margins : literary and environmental studies in Africa - Caminero-Santangelo, Byron, 1961- (Ohio University Press, 2011)
Environment at the Margins brings literary and environmental studies into a robust interdisciplinary dialogue, challenging dominant ideas about nature, conservation, and development in Africa and exploring alternative narratives offered by writers and environmental thinkers. The essays bring together scholarship in geography, anthropology, and environmental history with the study of African and colonial literatures and with literary modes of analysis. Contributors analyze writings by colonial administrators and literary authors, as well as by such prominent African activists and wr.